Blackwater versus Blackbeard : which international regulations exist for the use of private maritime security companies in vessel protection operations? - Wirtz, Christian Cornelius (Shipping Law Unit, 2016)
The problem of piracy and armed robbery at sea has sharply risen in the last decades. As a result, shipping companies, governments, insurances and maritime organisations have tried to approach the problem in different ways, the employment of private maritime security companies being one of them. State navies do not have enough resources to cover the vast areas of the high seas. As a result, armed security teams are exercising traditional State functions to protect vessels from being attacked. This study aims to find the legal foundations in international public law for the employment of armed guards on-board of commercial or private vessels. Furthermore, legal questions about the seizing of pirates, the use of force, criminal jurisdiction on-board of ships and the carrying of weapons will be scrutinized. For this purpose, the applicability of the Geneva Conventions and other key documents of the international humanitarian law will be analysed such as the Montreux Document and the Draft International Convention on the Regulation, Oversight and Monitoring of Private Military and Security Companies. Moreover, relevant aspects of the UNCLOS rules will be highlighted. An additional chapter will review existing international and regional soft law standards, mainly developed by the shipping and the security industry. The analysis concludes that international law has not yet developed distinct rules for the use of private maritime security companies. Especially the UNCLOS does not deal with private actors in the fight against piracy at all. As a result, national law remains responsible for the creation of a comprehensive set of rules concerning the employment and the conduct of maritime security guards. In addition, the vast number of soft law guidance and standards are missing enforceable and effective mechanisms and cannot yet be seen as an alternative for national regulations.